The shards - Ellis, Bret Easton (Alfred A. Knopf, 2023)
"A story about the end of innocence, and the perilous passage from adolescence into adulthood, set in a vibrantly fictionalized Los Angeles in 1981 as a serial killer begins targeting teenagers throughout the city"--